Evaluating STC2 gene RNA in peripheral blood serum of gastric cancer patients : STC2 gene and gastric cancer - Qiu, Junqi; Chen, Xihan; Zheng, Zengpai (Cellular and Molecular Biology, 2023)
Cancer is one of the leading causes of death in the world. Invasive microscopic and endoscopic methods are not suitable for routine screening of gastric cancer. Therefore, the need for biomarkers that can detect quickly, efficiently, and with high sensitivity in the early stages of cancer is strongly felt. Stanniocalcin plays a role in regulating calcium and phosphorus in the body. In addition, it plays a role in neuron cell differentiation, angiogenesis, wound healing, fertility and embryo development, and cancer. This study investigated the level of expression of the Stanniocalcin 2 (STC2) gene in the serum of patients with gastric cancer. This case-control study was conducted on the samples of 60 patients with gastric cancer (cases) and 60 healthy individuals (controls). Peripheral blood samples from gastric cancer patients and volunteers as control groups were collected in tubes containing EDTA anticoagulant and were immediately subjected to serum separation. After centrifugation, serum RNA was extracted, and after cDNA synthesis, STC2 gene serum RNA level was measured by the Taq Man method and Real-time PCR using specific primers and probes. Then, the results of serum evaluations and clinicopathological information of patients and control group were collected along with the information obtained from reviewing patients' files and demographic findings, regulatory tables, and related charts. SPSS22 software was used to analyze descriptive data. According to the study results, the high expression of the STC2 gene was 31 cases in the case group and 13 cases in the control group. However, there was a significant relationship between the high expression of the STC2 gene and gastric cancer (p = 0.0001). However, there was no significant relationship between the gender of patients and high expression of the STC2 gene. However, the age of 35% of the patients was more than 65 years, and there was a significant relationship between the age of the patients and the high expression of the STC2 gene (P = 0.028). Although there was no significant relationship between the anatomical location of the cancer and the subtypes of the cancer and the high expression of the STC2 gene, there was a significant relationship between the degree of cancer differentiation and the high expression of STC2 gene (P<0.05). In general, STC2 can be used as a biomarker to determine the border and margins of the tumor. Analysis of STC2 gene expression during surgery can reduce surgical error in tumor removal and increase the success of surgery for tumor removal.